Learning SQL server reporting services 2012 - Krishnaswamy, Jayaram (Birmingham : Packt Pub., 2013)
The book is packed with clear instructions and plenty of screenshots, providing all the support and guidance you will need as you begin to generate reports with SQL Server 2012 Reporting Services. This book is for those who are new to SQL Server Reporting Services 2012 and aspiring to create and deploy cutting edge reports. This book is for report developers, report authors, ad-hoc report authors and model developers, and Report Server and SharePoint Server Integrated Report Server administrators. Minimal knowledge of SQL Server is assumed and SharePoint experience would be helpful.
Hands-on exercise 3.2 -- turn the Reporting Service on/off in SSMS.
Includes index.
"Get the most out of SQL Server reporting service 2012, both Native and SharePoint integrated modes."
Master record variable field(s) change: 072
Keywords: SQL server; Microsoft SharePoint (Electronic resource); Microsoft SharePoint (Electronic resource); SQL server; COMPUTERS -- Databases -- General; Database management; Client/server computing; Client/server computing; Database management; Electronic books